Global burden on drug use disorders from 1990 to 2021 and projections to 2046 - Dongying, Chen; Yanyan, Sun; Xiaowu, Li; Zongyi, Yin (Frontiers in Public Health, 2025)
BackgroundDrug use disorders (DUDs) continue to pose a heavy burden on individuals, families, and societies. Despite extensive research, there remains a paucity of comprehensive reports on the spatiotemporal distribution, driving factors, and future trends of DUDs at global, regional, and national levels. This study aims to address this gap by investigating these critical aspects of the DUDs epidemic.Methods and findingsAnnual data on DUDs-related burden were collected from the Global Burden of Diseases, injuries, and risk factors Study (GBD) 2021. Age-period-cohort (APC) analysis and estimated annual percentage change were used to evaluate the spatiotemporal trend of burden. Decomposition analysis was used to identify the temporal and population-specific variations in the burden. The slope index of inequality and the concentration index were utilized to summarize health inequality of the burden. Frontier analysis was performed to evaluate the relationship between the burden of DUDs and socio-demographic development. The Nordpred model and Bayesian age-period-cohort (BAPC) model were introduced to forecast the burden. In 2021, the global prevalence of DUDs reached 53,115,936 (95% UI: 46,999,805–60,949,054), marking a 35.50% increase since 1990 and is projected to continue rising over the next 25 years. The increment in incidence, deaths, and disability-adjusted life years (DALYs) was 35.50%, 122.22%, and 74.65%, respectively. Despite the declining trends in global rates of incidence, prevalence, and DALYs, mortality still shows an upward trend, increasing from 1.26 to 1.65 per 100,000. Opioid and cocaine use disorders were the primary contributors to the overall increase in DUDs DALYs (82.07 and 59.57%, respectively). Population growth was the primary driver of the increase in DUDs DALYs (35.31%). A higher burden was observed in males and populations aged 15–39 years. Health inequality and insufficient healthcare performance regarding DUDs remain prominent issues in both high and low socio-demographic index (SDI) regions.ConclusionsThis study underscores the persistent and evolving nature of DUDs. Future research should focus on understanding the complex interplay between age and gender disparities, socioeconomic development, drug policies, and DUDs burden to inform more effective global strategies.